Challenges and future directions in photoelectro-Fenton techniques: A comprehensive review of emerging applications and innovations - Dakhil, Ihsan H.; Abbas, Ammar S. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
This comprehensive review examines the fundamental principles and practical applications of heterogeneous electrochemical wastewater treatment utilizing Fenton’s reactions. The fundamental equations involved in generating hydroxyl-free radicals in electro-Fenton and photoelectro-Fenton processes have been reviewed. Photoelectro-Fenton processes have been proven to be the most effective methods for mineralizing and degrading pollutants in wastewater. The primary focus is on understanding the limitations of hybrid Fenton processes and proposing practical solutions to address these challenges. Additionally, the study evaluated the significance of electrode configuration development and light penetration enhancement in promoting hydrogen peroxide production and enhancing hydroxyl radical generation. These improvements contribute to the enhanced degradation and mineralization of contaminants in groundwater. A comparative analysis of electrode materials, novel reactor configurations, and operating conditions demonstrates the relationship between preparation methods and treatment efficiency. Research gaps for improving the photoelectro-Fenton process are identified, with suggestions for future work. Studies have shown that internal light irradiation leads to higher removal efficiency compared to external lighting systems with the same light source power. The most important recommendations were utilizing multi-electrode stacked reactors to reduce energy consumption, enhancing current efficiency, the shape of the electrodes also plays a vital role in increasing light exposure on the photoanode surfaces, and conducting long-term experiments with various contaminants to demonstrate the reactor’s stability, efficiency, and efficacy in treating industrial wastewater.